Synthesis of 2,4,6-Triazidopyridine and Its 3,5-Diiodo Derivative - Chapyshev, Sergei V.; Chernyak, Alexander V. (Synthesis, 2012)
2,4,6-Trifluoropyridine was diiodinated with a mixture of potassium iodide and periodic acid in sulfuric acid at 55 °C to give 2,4,6-trifluoro-3,5-diiodopyridine in 85% yield. Both the starting trifluoropyridine and its 3,5-diiodo derivative readily react with excess sodium azide in dimethyl sulfoxide at room temperature to afford 2,4,6-triazidopyridine and 2,4,6-triazido-3,5-diiodopyridine in high yields. In the 15N NMR spectra of the triazides, the Nα atoms of the α- and γ-azido groups show very differing chemical shifts, which indicates the different reactivity of these groups in 1,3-dipolar cycloaddition, phosphorylation, reduction, thermolysis, and photolysis reactions.
Keywords: fluoropyridines; iodination; triazidation; azides; cross-linking reagents